Contemporary British fiction and the artistry of space style, landscape, perception - James, David 1979- (Continuum literary studies series, 2008)
"This study examines the importance of space for the way contemporary novelists experiment with style and form, offering an account of how British writers from the past three decades have engaged with landscape description as a catalyst for innovation. David James considers the work of more than fifteen major British novelists to offer a wide-ranging and accessible commentary on the relationship between landscape and narrative design, demonstrating an approach to the geography of contemporary fiction enriched by the practice of aesthetic criticism. Moving between established and emerging novelists, the book reveals that spatial poetics allow us to chart distinctive and surprising affinities between practitioners, showing how writers today compel us to pay close attention to technique when linking the depiction of physical places to new developments in novelistic craft." --Book Jacket